Nexus Between Green Finance & Green Economic Growth in G-20 Economies: Moderating Role of Environmental Governance (Journal of Asian Development Studies, 2025)
Green economic growth is crucial for achieving long-term sustainability, as it promotes resource efficiency, reduces carbon emissions, and fosters investments in environmentally friendly technologies. With climate change and environmental degradation posing significant global challenges, green finance has emerged as a key driver for sustainable economic transitions. This study is essential as it provides empirical insights into how green finance contributes to economic growth and how governance mechanisms shape this relationship, offering valuable policy recommendations for sustainable development. This study utilizes secondary panel data spanning 1995–2021 from G-20 countries to examine the relationship between green finance and green economic growth. A series of statistical tests is applied to analyze this relationship, with a particular focus on the moderating role of environmental governance in shaping the impact of green finance on economic sustainability. The results reveal a significant positive correlation between green finance and green economic growth. Green finance optimizes resource utilization, enhances energy productivity, and fosters investments in environmentally sustainable projects, ultimately reducing carbon emissions and mitigating environmental impacts. However, environmental governance exerts a negative moderating effect, indicating that stringent and inefficient institutional frameworks can hinder the benefits of green finance. The study underscores the need for improved governance mechanisms, transparency in green financial instruments, and policies that encourage sustainable economic behavior. This study contributes to the existing literature by providing empirical insights into the interplay between green finance, governance, and economic growth, offering valuable implications for policymakers and stakeholders in sustainable development.